2008
DOI: 10.1007/s10461-008-9490-1
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in HIV-Related Coping and Depression

Abstract: Our study examined differences in HIV-related coping in relation to depression in men and women. Ethnically diverse participants (n = 247, 46% women) were recruited in Dallas/Fort Worth and completed medical and demographic information, the Coping with HIV Scale (CHIV), and the Center for Epidemiological Studies-Depression scale (CES-D). Multiple regression analyses revealed that in men, depression was associated with symptoms, higher use of distraction, blame, expression and lower use of positive growth. In w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 37 publications
0
22
1
Order By: Relevance
“…If replicated, this finding may have important implications for AIDS researchers and clinicians. As others have noted, previous adherence investigations using combined gender samples may have obscured psychosocial mechanisms unique to women [39,40]. The results of the present study suggest that AIDS researchers may wish to stratify samples by gender, rather than merely controlling for gender effects [40].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…If replicated, this finding may have important implications for AIDS researchers and clinicians. As others have noted, previous adherence investigations using combined gender samples may have obscured psychosocial mechanisms unique to women [39,40]. The results of the present study suggest that AIDS researchers may wish to stratify samples by gender, rather than merely controlling for gender effects [40].…”
Section: Discussionmentioning
confidence: 53%
“…In contrast, Johnson and colleagues found that only 17% of older adults skipped ART doses in a 7-day period [17]. Similarly, older adults in Silverberg et al's study evinced higher rates of sustained adherence compared to younger (18-39 years) and middle-aged (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50) year old) patients [7]. In contrast, the majority of adherence studies have found an association between youth and poor adherence to ART.…”
Section: Introductionmentioning
confidence: 86%
“…According to Vosvick and colleagues [5], across multiple samples of PLWHA, it is evident that men and women differ in symptoms, behaviors, and other conditions, which greatly influences well-being. Nevertheless, studies examining if gender differences might have an impact on QoL domains are lacking.…”
Section: Psychopathological Symptomsmentioning
confidence: 99%
“…Despite the fact that gender and age are important markers for individual differences in psychosocial and life situation variables [4,5], to our knowledge, no published studies directly compare men's quality of life (QoL) and mental health to women's QoL and mental health, within the same sample and across age. Therefore, in the current study we intended to assess QoL gender and age differences, as well as possible interaction effects of age by gender, and the additional impact of psychopathological symptoms on QoL domains.…”
Section: Introductionmentioning
confidence: 99%
“…The most welldeveloped aspect of this literature has been focused on coping with the HIV/AIDS illness and other life stressors (e.g., Commerford et al 1994;Perez et al 2009;Vosvick et al 2010). Yet, there has been little investigation of other cognitive-affective factors related to these negative emotional states.…”
Section: Introductionmentioning
confidence: 99%